Laser induced surface structuring of Cu for enhancement of field emission properties. (21st February 2018) - Akram, Mahreen; Bashir, Shazia; Jalil, Sohail Abdul; Rafique, Muhammad Shahid; Hayat, Asma; Mahmood, Khaliq
Abstract: The effect of Nd:YAG (1064 nm, 10 ns, 10 Hz) laser induced surface structuring of copper (Cu) for enhancement of field emission (FE) properties has been investigated. X-ray diffraction analysis was employed to investigate the surface structural and compositional modifications. The surface structuring was explored by scanning electron microscope investigation. FE properties were studied under UHV conditions in a parallel plate configuration of planar un-irradiated Cu anode and laser irradiated Cu cathode. The Fowler–Nordheim plots were drawn to confirm the dominance of FE behavior of the measured I – V characteristics. The obtained values of turn-on field ' E o ', field enhancement factor ' β ' and maximum current density ' J max ' come out to be to be in the range of 5.5–8.5 V μ m −1, 1380–2730 and 147–375 μ A cm −2 respectively for the Cu samples irradiated at laser irradiance ranging from 13 to 50 GW cm −2 . The observed enhancement in the FE properties has been correlated with the growth of various surface structures such as ridged protrusions, cones and pores/tiny holes. The porous morphology is found to be responsible for a significant enhancement in the FE parameters.